PEMODELAN APLIKASI MOBILE PELAYANAN PUBLIK DESA (SMART VILLAGE) BERBASIS CLOUD COMPUTING - Rabby Nazli (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2019)
Public service is a necessity that can not be negotiated in improving the quality of service every time, every agency or organization that provides public services certainly wants to provide the best service to everyone it serves. At present public services in the village Beringin Taluk Kec. Kuantan Tengah District Kuantan Singingi has done very well but there are some obstacles in terms of public services such as the absence of a safe data storage place so that data is easily lost and damaged. There is no integration between BUMDes in the village so that information cannot be reviewed periodically. There is no integrated media of information or complaints, so people need to come directly to the village office to find information and provide complaints. Modeling an application for cloud computing-based public services has contributed to increasing the achievement of the goals of a village to get to a smart village with an integrated system and facilitate the community to access all needs in terms of information and services.